The influence of isometric muscle force characteristics on swimming results - Durovic, D.; Popovic, S.; Nikolic, M.; Szajer, P.; Madic, D.; Okicic, T. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of this research was to determine the influence of muscle force on swimming results. Thirteen male frestyle swimmers (Age=16.9 +/- 1.5 yrs; Height=179.1 9 +/- 6.9 cm; Weight=68.49 +/-9.0kg; FINA Points Scoring 2017 . 50 and 100 m freestyle long course = 572.0 9 +/- 80.8; n = 13) performed an upper (hand grip), lower body (half -squat) and lower back (dead-lift) isometric muscle test. The sample of variable system included eight variables for the estimation of muscle concractile potential of knee extensor (EK_Fmax, EK_FmaxREL), the extensor of lower back muscle (EL_Fmax, EL_FmaxREL) and muscle potential of dominant hand grip (SD_Fmax, SD_FmaxREL), while for the estimation of the swimming results at 50 and 100 meters free, one variable was used (FINA points 2017). For the measurement of maximum muscle force of back extensors and knee extensor a Japanese digital force measuring device .IMADA 32x-1100 with the software program WinW"udge 3.4 was used. For the measurement of dominant hand grip maximum force PAT2 (Physical Ability Test) device was used. The swimming results was presented in FINA points 2017. The data obtained by this research were processed by the statistics package "SPSS 19". For all the variables, the descriptive statistics and the regression analyses were used in order to determine the influence of muscle force to the swimming results. The results of regression analyses showed the significant statistical influence of the muscle force on swimming results (the muscle potential of the knee extensors, F= 5.454, p= 0.025; the muscle potential of back extensors F= 4.740, p= 0.036 and the muscle potential of hand grip, F= 5.526, p= 0.024). The obtained results indicate that the swimming results at 50 and 100 meters free directly depends on the variables who represent upper body, lower body and lower back muscle potential, respectively.